Immunogenicity and predictors of response to a single dose trivalent seasonal influenza vaccine in multiple sclerosis patients receiving disease‐modifying therapies. (25th July 2018) - Metze, Christoph; Winkelmann, Alexander; Loebermann, Micha; Hecker, Michael; Schweiger, Brunhilde; Reisinger, Emil Christian; Zettl, Uwe Klaus
Summary: Aims: To evaluate the immunogenicity and safety of a seasonal influenza vaccine in a cohort of multiple sclerosis (MS) patients receiving different immunomodulating/immunosuppressive therapies and assess predictors of immune response. Methods: A prospective, multicenter, non‐randomized observational study including 108 patients receiving a trivalent seasonal influenza vaccination was conducted. Influenza‐specific antibody titers (H1N1, H3N2, and influenza B) were measured to evaluate rates of seroprotection and seroconversion/significant titer increase. Univariable and multivariable analyses were performed to identify prognostic factors of vaccination outcomes. Results: Regarding the whole cohort, seroprotection rates >70% were achieved for each influenza strain. Interferon‐treated patients reached high seroprotection rates (>84%). Good seroprotection rates were seen in patients treated with glatiramer acetate. In particular for H3N2, response rates were low in natalizumab‐treated patients and in the small subgroup of fingolimod‐treated patients. Patients with a previous disease‐modifying therapy and a longer disease duration were less likely to respond sufficiently. No severe adverse events were reported. MS disease activity was not increased after a one‐year follow‐up period. Conclusion: Vaccination led to good immunogenicity, especially in MS patients treated with interferons and glatiramer acetate. At least for the H1N1 strain, rates of seroprotection and seroconversion/significant titer increase were high (>70% and >60%, respectively) for all therapeutic subgroups. Patients with a longer duration of the disease are exposed to an increased risk of insufficient immune response to vaccination.